A Wire-Shaped Supercapacitor in Micrometer Size Based on Fe3O4 Nanosheet Arrays on Fe Wire - Li, Guohong; Li, Ruchun; Zhou, Weijia (Nano-Micro Letters, 2017)
One-dimensional (1D, wire- and fiber-shaped) supercapacitors have recently attracted interest due to their roll-up, micrometer size and potential applications in portable or wearable electronics. Herein, a 1D wire-shaped electrode was developed based on Fe3O4 nanosheet arrays connected on the Fe wire, which was prepared via oxidation of Fe wire in 0.1 M KCl solution (pH 3) with O2-rich environment under 70 °C. The obtained Fe3O4 nanosheet arrays displayed a high specific capacitance (20.8 mF cm−1 at 10 mV s−1) and long cycling lifespan (91.7% retention after 2500 cycles). The excellent performance may attribute to the connected nanosheet structure with abundant open spaces and the intimate contact between the Fe3O4 and iron substrate. In addition, a wire-shaped asymmetric supercapacitor was fabricated and had excellent capacitive properties with a high energy density (9 µWh cm−2) at power density of 532.7 µW cm−2 and remarkable long-term cycling performance (99% capacitance retention after 2000 cycles). Considering low cost and earth-abundant electrode material, as well as outstanding electrochemical properties, the assembled supercapacitor will possess enormous potential for practical applications in portable electronic device. Highlights: 1 Fe3O4 nanosheet arrays were successfully assembled on one-dimensional Fe wire by a simple one-step oxidization treatment. 2 The Fe@Fe3O4 electrode displays a high specific capacitance of 20.8 mF cm−1 at 10 mV s−1. 3 A wire-shaped supercapacitor (WSSC) based on Fe@Fe3O4 was assembled, and it exhibited a high energy density (9 µWh cm−2 at 532.7 µW cm−2) and good stability.